2023
DOI: 10.3389/fmars.2023.1104786
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface dispersion path and travel time of radiocesium from Fukushima by Mode Water

Abstract: The Fukushima Daiichi Nuclear Power Plant (FDNPP) accident on March 11, 2011 resulted in the release of immense amounts of radioactive materials into the ocean. However, the dispersion of radioactive materials in the subsurface has not yet been clarified due to the spatiotemporal limitation of observations. Thus, herein, a tracer experiment was implemented using a three-dimensional numerical model to estimate the dispersion path of 137Cs released directly from the FDNPP and its travel time in the subsurface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…However, it should be noted that the temperature (15°C–18°C) of samples in the WPBCA is slightly lower compared with the original STMW (16°C–19°C) in the northern NPSG. This suggests that the water with high Cs activity concentration may be influenced during the formation of the Cs maximum layer, especially during the water subduction near the Kuroshio extension region (Oka et al., 2015), and is a large portion of original STMW in the NPSG (Lee et al., 2023). The formation processes of the Cs maximum water in the STMW are out of the scope of this study, and could be further discussed in future research.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that the temperature (15°C–18°C) of samples in the WPBCA is slightly lower compared with the original STMW (16°C–19°C) in the northern NPSG. This suggests that the water with high Cs activity concentration may be influenced during the formation of the Cs maximum layer, especially during the water subduction near the Kuroshio extension region (Oka et al., 2015), and is a large portion of original STMW in the NPSG (Lee et al., 2023). The formation processes of the Cs maximum water in the STMW are out of the scope of this study, and could be further discussed in future research.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study using a 3-dimensional hydrodynamic model (Lee et al, 2023), it was reported that a radioactive tracer originating from the FDNPP took approximately 8-9 years to reach the Taiwan and Philippine islands and followed a clockwise trajectory; however, there may have been limited southward movement that dissipated rapidly. This main propagation indicates a relatively longer travel time compared to previous studies (Behrens et al, 2012;Aoyama et al, 2018;Inomata et al, 2018;Wang et al, 2022) because they consider the limitation associated with the minimum concentration of 0.01 Bq m -3 of the tracer dyne method.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Subducted radioactive materials within the NPSTMW spread into the subtropical region of the North Pacific (Men et al, 2015;Cedarholm et al, 2019;Lee et al, 2023). Men et al (2015) reported that 134 Cs was found at 21.50°N, 125.00°E at a depth of 200 m near Taiwan Island after monitoring the area between 2011 and 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates the widespread dispersal of pollutants and their insertion into the marine food chain, raising concerns about the long-term ecological consequences. The ocean's capacity to neutralize and dissipate radionuclides does not completely mitigate environmental risks (Lee et al, 2023). These substances might gather in speci c areas due to oceanic processes, resulting in irradiation "hotspots" that may harm local marine life.…”
Section: Wavelengths Of Radiation and Oceanic In Uencementioning
confidence: 99%